(untitled) (Fiep Bulletin - online, 2012)
This research aims to assess the degree of hip flexibility of academic degree in Physical Education in the region of Foz do Iguaçu. METHODS: The survey sample consisted of 36 individuals, aged between 18 and 25 years, 19 men and 17 women. Before data collection all participants completed a case history sheet, which contained questions about the amount of time you exercise for trained and flexibility. To collect data we used a Fleximeter Sanny, using the evaluation protocol of flexibility (MONTEIRO, 2000). RESULTS: The average flexibility of the men was assessed in 92.3 (± 13.8) degrees to the left hip, right hip and 85.7 (± 14), and flexibility of the medium was evaluated in 90 women, 8 (± 11.3) degrees to the left hip and 88 (± 11.4) degrees to the right hip. CONCLUSION: The available literature shows that flexibility is a key parameter for the functionality of the human locomotor system (Vilarba, 2007), all individuals should be concerned about the levels of this parameter is one of those who are part of health-related fitness . the Academy of Physical Education should understand that they are opinion leaders, especially in relation to physical activity, and this study shows that many are forgetting that flexible working is also a form of physical activity.